2014
DOI: 10.1017/s0025315414000459
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal changes in size, sex-ratio and body condition of the damselfishChromis chromisin the central Mediterranean Sea

Abstract: 3Current address: School of Biological and Chemical Sciences, The University of the South Pacific, Laucala Campus, Private Mail Bag, Suva, FijiChromis chromis is one of the most abundant fish species on the Mediterranean rocky shores. Acting as a by-pass of nutrients from the pelagic to the rocky littoral system, it plays an important role as a resource provider and has a relevant function in the community assemblage. Chromis chromis has many of the characteristics required of an indicator species (e.g. it is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…An unequal sex ratio was observed for C. notata , probably attributable to the reproductive behavior of pomacentrid fish. Males migrate to the bottom and are involved in parental care during the spawning period (Ochi, ; Bracciali, Piovano, Sara, & Giacoma, ). The spawning period for C. notata was from June to August, as reported in Go and Jeon (); Suzuki, Hioki, and Kurita (); and Lee and Lee ().…”
Section: Discussionmentioning
confidence: 99%
“…An unequal sex ratio was observed for C. notata , probably attributable to the reproductive behavior of pomacentrid fish. Males migrate to the bottom and are involved in parental care during the spawning period (Ochi, ; Bracciali, Piovano, Sara, & Giacoma, ). The spawning period for C. notata was from June to August, as reported in Go and Jeon (); Suzuki, Hioki, and Kurita (); and Lee and Lee ().…”
Section: Discussionmentioning
confidence: 99%
“…Age, growth and mortality of C. chromis were described by Dulčić & Kraljević () and individual size, sex‐ratio and body condition were all explored by Bracciali et al . ().…”
Section: Introductionmentioning
confidence: 97%
“…Dulčić & Kraljević (1994) showed that C. chromis fecundity (the number of mature eggs) increased exponentially with fish age-length and that females become sexually mature at 6·8-7·3 cm L T as they approached age 2 years. Age, growth and mortality of C. chromis were described by Dulčić & Kraljević (1995) and individual size, sex-ratio and body condition were all explored by Bracciali et al (2014). Chromis chromis has a long history of scientific investigation (Cooper & Santini, 2006), it is one of only two damselfish species (family Pomacentridae) included in Linnaeus's Systema Naturae (1758), though referred to at the time as Sparus chromis.…”
Section: Introductionmentioning
confidence: 99%
“…The Mediterranean damselfish Chromis chromis (L. 1758) is characterized by male nest defence. This is a small (average standard length, L S = 6 cm; Bracciali et al ., ), sexually monomorphic species commonly distributed in the Mediterranean Sea, extending to the eastern part of the Atlantic Ocean. It lives in shoals near rocky reefs or above seagrass meadows at depths between 3 and 30 m (Lythgoe & Lythgoe, ; Quignard & Pras, ).…”
Section: Introductionmentioning
confidence: 99%